La fabricación digital como herramienta de educación inclusiva para personas con discapacidad visual: análisis literario y bibliométrico - Carrión Puelles, Naldi Susan (2022)
Technology integration in teaching people with disabilities is essential and has generated the so-called assistive technologies. Among them, digital manufacturing technologies, considered transformative, have made personalization faster and access easier and more affordable, mainly for the visually impaired. This research combines a literature review with bibliometrics to evaluate the application of digital fabrication technologies in the learning process of students with visual disabilities. Likewise, it analyzes its contribution to implementing explicit instruction, a fundamental and transversal methodology for teaching people with and without visual disabilities. It offers a multisensory educational experience and can potentially increase the number of inclusive educational spaces.